Structured headache services as the solution to the ill-health burden of headache. 3. Modelling effectiveness and cost-effectiveness of implementation in Europe: findings and conclusions - Tinelli, Michela; Leonardi, Matilde; Paemeleire, Koen; Raggi, Alberto; Mitsikostas, Dimos; de la Torre, Elena Ruiz; Steiner, Timothy J. (Journal of headache and pain, 2021)
Background There have been several calls for estimations of costs and consequences of headache interventions to inform European public-health policies. In a previous paper, in the absence of universally accepted methodology, we developed headache-type-specific analytical models to be applied to implementation of structured headache services in Europe as the health-care solution to headache. Here we apply this methodology and present the findings. Methods Data sources were published evidence and expert opinions, including those from an earlier economic evaluation framework using the WHO-CHOICE model. We used three headache-type-specific analytical models, for migraine, tension-type-headache (TTH) and medication-overuse-headache (MOH). We considered three European Region case studies, from Luxembourg, Russia and Spain to include a range of health-care systems, comparing current (suboptimal) care versus target care (structured services implemented, with provider-training and consumer-education). We made annual and 5-year cost estimates from health-care provider and societal perspectives (2020 figures, euros). We expressed effectiveness as healthy life years (HLYs) gained, and cost-effectiveness as incremental cost-effectiveness-ratios (ICERs; cost to be invested/HLY gained). We applied WHO thresholds for cost-effectiveness. Results The models demonstrated increased effectiveness, and cost-effectiveness (migraine) or cost saving (TTH, MOH) from the provider perspective over one and 5 years and consistently across the health-care systems and settings. From the societal perspective, we found structured headache services would be economically successful, not only delivering increased effectiveness but also cost saving across headache types and over time. The predicted magnitude of cost saving correlated positively with country wage levels. Lost productivity had a major impact on these estimates, but sensitivity analyses showed the intervention remained cost-effective across all models when we assumed that remedying disability would recover only 20% of lost productivity. Conclusions This is the first study to propose a health-care solution for headache, in the form of structured headache services, and evaluate it economically in multiple settings. Despite numerous challenges, we demonstrated that economic evaluation of headache services, in terms of outcomes and costs, is feasible as well as necessary. Furthermore, it is strongly supportive of the proposed intervention, while its framework is general enough to be easily adapted and implemented across Europe.